(untitled) (Fiep Bulletin - online, 2011)
This study aimed to determine the influence of initiation in the sport of soccer motor development male children aged 11 to 13 years, by applying a battery of tests (100-yard speed, agility shuttle run and standing long jump) and verification of measures of height and weight. The total population was 13 (thirteen) children. After applying the test and verification of measures were obtained the following data: in anthropometric characteristics can be observed that the children are in development stage more advanced than the optimal (School of Public Health Harvard) and tests of motor performance, compared with average graphics and great for every age group as Gallahue (2003), The test of the speed of 100 yards, it was noted that 63% of children were able to finish the test with a score below the ideal score, 36% exceeded the ideal score. In the Shuttle Run test: only 27% of children were below the ideal score and 55% exceeded the ideal score, getting 18% of children within the ideal score of the test. And at last the Horizontal Impulse: this test was the balanced 45% of children surveyed achieved a score below the optimal level, 45% were above the ideal score and 10% will attain the ideal score for age. According to the data obtained by measurements and applications of tests we can conclude that the majority of children who regularly practice a sport, in case soccer, show significant gains in the development of motor skills.